Cancer-Immunity Cycle and Therapeutic Interventions- Opportunities for Including Pet Dogs With Cancer - Von Rueden, Samantha K.; Fan, Timothy M. (Frontiers in Oncology, 2021)
The tumor-immune interplay represents a dynamic series of events executed by cellular and soluble participants that either promote or inhibit successful tumor formation and growth. Throughout a tumor’s development and progression, the host organism’s immune system reacts by generating anti-cancer defenses through various incremental and combinatorial mechanisms, and this reactive orchestration is termed the cancer-immunity cycle. Success or failure of the cancer-immunity cycle dictates the fate of both host and tumor as winner or loser. Insights into how the tumor and host immune system continuously adapt to each other throughout the lifecycle of the tumor is necessary to rationally develop new effective immunotherapies. Additionally, the evolving nature of the cancer-immunity cycle necessitates therapeutic agility, requiring real-time serial assessment of immunobiologic markers that permits tailoring of therapies to the everchanging tumor immune microenvironment. In order to accelerate advances in the field of immuno-oncology, this review summarizes the steps comprising the cancer-immunity cycle, and underscores key breakpoints in the cycle that either favor cancer regression or progression, as well as shaping of the tumor microenvironment and associated immune phenotypes. Furthermore, specific large animal models of spontaneous cancers that are deemed immunogenic will be reviewed and proposed as unique resources for validating investigational immunotherapeutic protocols that are informed by the cancer-immunity cycle. Collectively, this review will provide a progressive look into the dynamic interplay between tumor and host immune responses and raise awareness for how large animal models can be included for developing combinatorial and sequenced immunotherapies to maximizing favorable treatment outcomes.